THE ROLE OF ENGLISH AS A GLOBAL LANGUAGE IN INTERNATIONAL COMMUNICATION - Sabrina Abdurahimova Abdullo qizi, (TADQIQOTLAR, 2026)
Abstract: The increasing interconnectedness of the modern world has led to the emergence of English as the dominant global language. This paper explores the role of English in facilitating international communication across various domains, including business, education, science, and diplomacy. Based on an analysis of existing scholarly literature,  the  study  examines  the  historical,  political,  and  economic  factors  that contributed to the global spread of English. It also evaluates the concept of English as a  lingua  franca  and  discusses  the  advantages  and  challenges  associated  with  its widespread use. The findings indicate that while English significantly enhances global interaction  and  access  to  information,  it  also  raises  concerns  related  to  linguistic inequality, cultural dominance, and the marginalization of local languages.